1999
DOI: 10.1007/pl00014336
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors of thrombophilia in ischaemic childhood stroke of cardiac origin. A prospective ESPED survey

Abstract: While FV G1691A and prothrombin G20210 A mutations show no significant data in our study, lipoprotein (a) levels >30 mg/dl protein C deficiency, anticardiolipin antibodies and combined prothrombotic disorders seem to be important risk factors for manifestation of ischaemic strokes in children with underlying cardiac disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 5 publications
1
73
0
2
Order By: Relevance
“…Results of available studies differ, mainly because of differences in the study populations, age groups, or study designs. [15][16][17][18][19][20][21][22][23][24][25] Very recently, we have shown that an increased Lp(a) level, the FV G1691A mutation, the PT 20210A allele, and the homozygous C677T polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene are significant risk factors for spontaneous stroke in childhood. 23 That study, however, did not include neonatal and child patients with additional acquired risk factors.…”
mentioning
confidence: 99%
“…Results of available studies differ, mainly because of differences in the study populations, age groups, or study designs. [15][16][17][18][19][20][21][22][23][24][25] Very recently, we have shown that an increased Lp(a) level, the FV G1691A mutation, the PT 20210A allele, and the homozygous C677T polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene are significant risk factors for spontaneous stroke in childhood. 23 That study, however, did not include neonatal and child patients with additional acquired risk factors.…”
mentioning
confidence: 99%
“…In older children with AIS, the data has been conflicting and has been hampered by the small number of cases in some of the published studies (Bonduel et al, 1999;McColl et al, 1999;Nowak-Gottl et al, 1999;Strater et al, 1999;Kenet et al, 2000). Nevertheless, there does seem to be a trend towards an increased incidence of prothrombotic abnormalities in older children with AIS Chan et al, 2000).…”
Section: Fetal and Neonatal Thrombophiliamentioning
confidence: 99%
“…in gestational weeks 10,20,30) to evaluate fetal growth development and to detect possible intrauterine fetal thrombus formation (caval/renal veins, cerebral arteries/veins) prior to delivery postnatal patterns of maturation. In the newborn, plasma concentrations of the vitamin K-dependent coagulation factors (II, VII, IX, X), contact factors (XI, XII, prekallikreine and high-molecular weight kininogen) are approximately 50% of adult values.…”
Section: Practice Pointsmentioning
confidence: 99%